NURSE MORALE AND SELF-REGULATION CORELLATION AT MENTAL HOSPITAL Dr. AMINO GONDHOHUTOMO SEMARANG - Aditha Fajrina; Sri Hartati (Jurnal EMPATI, 2014)
Self-regulation is the ability of a person to organize, direct and control her/himself in order to be persistently on the goal which is intended to reach and to be based on the desired standard. Morale is the working attitude of the employee which is realized into fervor, cooperation, and discipline. This research is intended to examine nurse morale and self-regulation at mental hospital Dr. Amino Gondhohutomo Semarang. The population of this research was nurses at mental hospital ward of Dr. Amino Gondhohutomo, with minimally one year working period, and less than 40 years old. The collection of research sample used simple random sample technique. The data collection instruments used were a scale consisted of morale scale from 28 valid items with the reliability coeffisient of 0.906 and self regulation from 23 valid items with reliability coeffisient of 0.872 which had been tested on 60 nurses of mental hospital of Dr. Amino Gondhohutomo Semarang. The result of simple linear regression analysis showed that coeffisient value of corellation between morale and self-regulation was 0.675 with p = 0.000 (p < 0.005). The corellation coeffisient which had possitive value showed that both variables direction were posstive, which meant that the higher the morale the higher the self-regulation was. On the contrary, the lower the morale, the lower the self-regulation. The effective contribution of morale with self-regulation was 45.5%. Such result indicated that there were 54.5% other factors.